PEMBERDAYAAN MASYARAKAT UNTUK MENINGKATKAN KESADARAN DAN PENGETAHUAN TENTANG HUKUM DI DESA CURUP GURUH KAGUNGAN - Izzah AlHadi; Mela Suhariyanti; Wulan Rahmadani; Amaliah Ramadhani; Kurniawan; Muhammad Alfath; Yudi Rahman (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2023)
Law is a rule or rule that binds or regulates society. Law is something that is closely related to human life which refers to the most important system in implementing law enforcement. Various attempts were made to overcome the problems that occurred, one of which was throught a legal counseling in the 2023 UMKO Knowledge Transfer KKN activities. Legal counseling is is a form of student contribution in the field of community service. Community service activities aim as a means for student to channel their concern for the people of Curup Guruh Kagungan Village so that they realize how important law is social life. The purpose of this activity is to help the community understand more about land rights and the importance of law for sicial life. This activity involved the people of Curup Guruh Kagungan Village from various allinces. The implementation of this legal counseling activity was carried out directly at the Curup Guruh Kagungan Village Hall. The result of this legal counseling activity were seen from the Curup Guruh Kagungan village community understoot or absobed the material presented by the two informants and the Curup Guruh Kagungan village community who asked about land rights and the importance of law to the spekeers.